(untitled) (Journal of Social Sciences Review, 2023)
Business schools appear to be under-researched when it comes to sexual harassment. Because of the hesitancy of victims to report their experiences, sexual harassment in academia is often a hidden issue. In the last few years, the media and research have paid great attention to it, and the general public is becoming more aware of it. This research work aimed to find out the students’ knowledge about sexual harassment, the types faced by students, and further, evaluate up to what extent sexual harassment impedes the academic performance of students. The study also aimed to find various elements leading to the sexual harassment experience of males and females in the classroom. The data of this qualitative study are collected through 30 semi-structured interviews from students of public and private business schools in Peshawar city. The study investigates the effect of sexual harassment on the academic performance of students. The results indicate that it affects the mental health and morale of students and it leads to dissatisfaction. Hence, there is a crucial need to develop sustainable systems to redress the structure through anti-sexual harassment policies.